Religion, Social Connectedness, and Xenophobic Responses to Ebola - Chuang, Roxie; Eom, Kimin; Kim, Heejung S. (Frontiers in Psychology, 2021)
This study examined the role of religion in xenophobic responses to the threat of Ebola. Religious communities often offer members strong social ties and social support, which may help members cope with psychological and physical threat, including global threats like Ebola. Our analysis of a nationally representative sample in the U.S. (N = 1,000) found that overall, the more vulnerable to Ebola people felt, the more they exhibited xenophobic responses, but this relationship was moderated by importance of religion. Those who perceived religion as more important in their lives exhibited weaker xenophobic reactions than those who perceived religion as less important. Furthermore, social connectedness measured by collectivism explained the moderating role of religion, suggesting that higher collectivism associated with religion served as a psychological buffer. Religious people showed attenuated threat responses because they had a stronger social system that may offer resources for its members to cope with psychological and physical threats. The current research highlights that different cultural groups react to increased threats in divergent ways.